2020
DOI: 10.3389/fncir.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Spinal Dorsal Horn Circuit Function and Dysfunction Using Optical Approaches

Abstract: Somatosensation encompasses a variety of essential modalities including touch, pressure, proprioception, temperature, pain, and itch. These peripheral sensations are crucial for all types of behaviors, ranging from social interaction to danger avoidance. Somatosensory information is transmitted from primary afferent fibers in the periphery into the central nervous system via the dorsal horn of the spinal cord. The dorsal horn functions as an intermediary processing center for this information, comprising a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 258 publications
(316 reference statements)
0
23
0
Order By: Relevance
“… 66 , 67 The mouse spinal cord is well-suited for optical techniques given its size and expanding understanding of the molecularly defined populations processing somatosensation. 19 , 68 , 69 We imaged activity-evoked changes in intracellular calcium using GCaMP6s and deconvolved activity using spike-inference algorithms built into the software CaImAn, an established methodology. 24 , 26 , 70 A recent imaging study demonstrated that calcium responses faithfully encode action potentials in lamina I in mice.…”
Section: Discussionmentioning
confidence: 99%
“… 66 , 67 The mouse spinal cord is well-suited for optical techniques given its size and expanding understanding of the molecularly defined populations processing somatosensation. 19 , 68 , 69 We imaged activity-evoked changes in intracellular calcium using GCaMP6s and deconvolved activity using spike-inference algorithms built into the software CaImAn, an established methodology. 24 , 26 , 70 A recent imaging study demonstrated that calcium responses faithfully encode action potentials in lamina I in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the site of modulation (pre‐ versus postsynaptic) is difficult because of the complexity of the system. Several complementary approaches have been used for this purpose, including electrophysiological and analytical procedures, optical recording, and opto‐ or chemogenetic stimulation of specific synaptic inputs (reviewed in Harding, Fung, & Bonin, 2020). The methods described in this article can help address this issue.…”
Section: Commentarymentioning
confidence: 99%
“…Indeed, selective primary afferent innervation of excitatory and inhibitory interneurons in the spinal dorsal horn allow for varied integration of incoming signals from the periphery. 67 Additionally, artificial single channel driven neuronal activation fails to recapitulate physiological neuronal firing and the change in thermal preference likely requires a host of other changes beyond an increase in the excitability of TrpV1 + afferents.…”
Section: Discussionmentioning
confidence: 99%